Airborne pollen from allergenic herbaceous plants in urban and rural areas of Western Pomerania, NW Poland. Issue 1 (2nd January 2017) - Kruczek, Aleksandra; Puc, MaŁgorzata; Wolski, Tomasz
Abstract: This paper presents the course of the pollen season of selected allergenic taxa ( Rumex spp., Plantago spp., Urtica spp . and Chenopodiaceae) in two towns with different degrees of urbanisation (urban, the city Szczecin, and rural, the village Gudowo in Western Pomerania, northwest Poland). The study was conducted in the years 2012–2014 with the volumetric method. The pollen of allergenic herbaceous plants was present in the air from early May until the end of September. From among the taxa studied, the genus Rumex is characterised by the longest pollination period, while the genus Urtica by the shortest. The highest percentage contribution of pollen grains to the total pollen count in the air reaching over 90% is from nettle. The pollen seasons determined for the majority of taxa are longer in the city, however the mean pollen grain counts in the air are higher for the rural area.